2013
DOI: 10.3109/08820538.2013.835835
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Diffuse Uveal Melanocytic Proliferation as a Precursor to Multiple Systemic Malignancies

Abstract: Bilateral diffuse uveal melanocytic proliferation (BDUMP) is a rare, intraocular paraneoplastic syndrome characterized by multiple, elevated, pigmented uveal lesions, diffuse thickening of the uveal tract, and rapidly progressive cataracts. We report a 70-year-old Caucasian male with an inferotemporal conjunctival-scleral pigmented lesion of the right eye. Funduscopy and ultrasonography revealed multiple elevated pigmented choroidal lesions in both eyes. Genome-wide single nucleotide polymorphism (SNP) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…They also looked for mutations in GNAQ, GNA11 and BRAF V600E in the BDUMP melanocytes, but did not demonstrate these. Rahimy et al [10] showed chromosome 5 gain in their case, and interestingly also described focal cytological atypia within the cells. The lack of GNAQ/GNA11 mutations in these 2 cases and in ours would suggest that if BDUMP represents a neoplastic process, it is one that possibly follows a different oncogenic pathway to uveal naevi and the majority of uveal melanomas [12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They also looked for mutations in GNAQ, GNA11 and BRAF V600E in the BDUMP melanocytes, but did not demonstrate these. Rahimy et al [10] showed chromosome 5 gain in their case, and interestingly also described focal cytological atypia within the cells. The lack of GNAQ/GNA11 mutations in these 2 cases and in ours would suggest that if BDUMP represents a neoplastic process, it is one that possibly follows a different oncogenic pathway to uveal naevi and the majority of uveal melanomas [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are over 50 cases of BDUMP reported in literature, only 3 of these have been evaluated for genetic alterations, with 2 of the 3 cases showing genetic abnormalities [8,10]. Mudhar et al [8] described gains in chromosome 6 and X, and deletions in chromosome 19 in the BDUMP case they analysed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations